Immediate Denture Fabrication Covering a Torus Palatinus - Rishu Koul; Guruprasada Upadhyay; Deepak Kalia; Kamal Verma (Journal of Primary Care Dentistry and Oral Health)
This case report elaborates on conventional immediate denture as treatment modality in partially edentulous patient with torus palatinus and periodontally compromised teeth, who desired no period of complete edentulousness. The prosthesis was designed to fulfill functional, cosmetic and psychological requirements immediately following the removal of remaining natural teeth. The case describes the delivery of complete denture immediately with no intermediate healing phase postextraction of remaining teeth and no surgical excision of torus palatinus.